Study of Urogenital Fistula in Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2018)
This cross-sectional study was carried out in the gynae department of Rajshahi Medical College Hospital during the year January 2005 to December 2011, where 202 patients were studied for obstetric history, previous attempt at repair, the condition of the patient, the route of repair, age, etiological factors, techniques of surgery, socio-economic conditions, as well as treatment & results. Among 202 cases, surgery was done in 136 cases (67.33%). Among them 126 were successful (92.65%) and 10 failed (9.35%). Obstetric fistula results from obstructed labour occur mostly in the first pregnancy in young women. Prevention will include education, communication, transport, health care measures and prevention of early marriage. Awareness for mandatory hospital delivery in high risk pregnancies also can reduce obstetric fistulas. With good pre-operative intra-operative and post operative care and attention to surgical details may cure these affected woman.TAJ 2011; 24(2): 91-94